Assessment of chemotherapy regimens on radiation pneumonitis in patients with unresectable stage III non‐small‐cell lung cancer after definitive chemoradiotherapy. Issue 13 (18th May 2021) - Sakaguchi, Tadashi; Ito, Kentaro; Furuya, Naoki; Morikawa, Kei; Fujiwara, Kentaro; Nishii, Yoichi; Inoue, Takeo; Hataji, Osamu; Mineshita, Masamichi
Abstract: Background: Consolidation therapy with durvalumab after concurrent chemoradiotherapy has been reported to significantly prolong progression‐free survival and overall survival in patients with stage III unresectable non‐small cell lung cancer (NSCLC). However, which chemotherapy regimen should be selected for consolidation therapy with durvalumab is currently unknown. Methods: We retrospectively reviewed consecutive patients with unresectable stage III NSCLC who received concurrent definitive chemoradiotherapy with platinum‐based chemotherapy. We reviewed the timing and severity of radiation pneumonitis by assessing chemotherapy regimens and histology. Results: A total of 103 patients were identified. Fourteen patients (13.6%) developed grade 2 or greater radiation pneumonitis within 42 days after chemoradiotherapy. No adenocarcinoma patients treated with a regimen of cisplatin plus pemetrexed developed grade 2 or greater radiation pneumonitis within 42 days; however, 20% of patients who were treated with carboplatin plus paclitaxel developed grade 2 or greater radiation pneumonitis. Furthermore, the objective response rates and disease control rates of cisplatin plus pemetrexed were equal to or greater than those of carboplatin plus paclitaxel in adenocarcinoma patients. Conclusion: Cisplatin plus pemetrexed regimen may be a preferable option to consider for subsequent consolidation therapy with durvalumab in patients with unresectable stage III adenocarcinoma. Abstract : Among a total of 103 patients with unresectable stage III NSCLC who received concurrent definitive chemoradiotherapy, 13.6% of patients developed grade 2 or greater radiation pneumonitis within 42 days after chemoradiotherapy. No adenocarcinoma patients treated with cisplatin plus pemetrexed developed grade 2 or greater radiation pneumonitis within 42 days; however, 20% of patients treated with carboplatin plus paclitaxel developed grade 2 or greater radiation pneumonitis.